Consumption of dairy product and its association with total and cause specific mortality – A population-based cohort study and meta-analysis. Issue 6 (December 2019) - Mazidi, Mohsen; Mikhailidis, Dimitri P.; Sattar, Naveed; Howard, George; Graham, Ian; Banach, Maciej; ,
Summary: Background: The intake of dairy products has been thought to be associated with an increased risk of coronary heart diseases (CHD) and total mortality due to its relatively high content of saturated fat. However, reports on this association particularly among US adults are conflicting and controversial. Therefore, we used data from the 1999–2010 National Health and Nutrition Examination Surveys (NHANES) study to examine whether consumption of total dairy and dairy subgroups was associated with total and cause specific (CHD, cerebrovascular and cancer) mortality. Further we carried out a systematic review and meta-analysis of prospective studies to check for consistency with the NHANES findings. Methods: In the NHANES cohort vital status through December 31, 2011 was ascertained. Cox proportional hazard regression models were used to relate baseline dairy intake with all-cause and cause-specific mortality. For the systematic review PubMed, SCOPUS, Web of Science and Google Scholar databases were searched (up to December 2017). The DerSimonian-Laird method and generic inverse variance methods were used for quantitative data synthesis. Results: In the NHANES data set of 24, 474 participants, 3520 deaths occurred during follow-up. In multivariate adjusted Cox models, total mortality risk was lower when comparing the top (Q4) with the lower (Q1) quartiles of total dairy (hazard ratio [HR] 0.98, 95% confidence interval [CI]: 0.95–0.99) and cheese (HR: 0.92, 95% CI: 0.87–0.97) consumption. Using a similar model, we have found a negative association between total dairy and milk consumption with risk of cerebrovascular mortality (HR: 0.96, 95% CI: 0.94–0.98, HR: 0.93, 95% CI: 0.91–0.96, respectively), while milk consumption was associated with increased CHD mortality (HR: 1.04, 95% CI: 1.02–1.06). The meta-analysis with 636, 726 participants indicated a significant inverse association between fermented dairy products and total mortality (RR: 0.97, 95% CI: 0.96–0.99), while milk consumption was associated with higher CHD mortality (RR: 1.04, 95% CI: 1.01–1.05). These findings were robust in sensitivity analyses. Conclusions: Among American adults, higher total dairy consumption was associated with lower total and cerebrovascular mortality, while higher milk consumption was associated with higher risk of CHD. These findings do not support dogmatic public health advice to reduce total dairy fat consumption, although the association between milk consumption and CHD mortality requires further study. Graphical abstract: Image 1